Answer:
A. ![x^2 = (4x - 1)^2 + (6x + 7)^2](https://tex.z-dn.net/?f=x%5E2%20%3D%20%284x%20-%201%29%5E2%20%2B%20%286x%20%2B%207%29%5E2)
Step-by-step explanation:
The question seems to be incomplete. However, we'll make the following assumption.
![Opposite = 6x + 7](https://tex.z-dn.net/?f=Opposite%20%3D%206x%20%2B%207)
![Adjacent = 4x - 1](https://tex.z-dn.net/?f=Adjacent%20%3D%204x%20-%201)
![Hypothenuse = x](https://tex.z-dn.net/?f=Hypothenuse%20%3D%20x)
Pythagoras theorem states that:
![Hypothenuse^2 = Opposite^2 + Adjacent^2](https://tex.z-dn.net/?f=Hypothenuse%5E2%20%3D%20Opposite%5E2%20%2B%20Adjacent%5E2)
Substitute values for Hypothenuse, Opposite and Adjacent.
This gives
![x^2 = (6x + 7)^2 + (4x - 1)^2](https://tex.z-dn.net/?f=x%5E2%20%3D%20%286x%20%2B%207%29%5E2%20%2B%20%284x%20-%201%29%5E2)
or
![x^2 = (4x - 1)^2 + (6x + 7)^2](https://tex.z-dn.net/?f=x%5E2%20%3D%20%284x%20-%201%29%5E2%20%2B%20%286x%20%2B%207%29%5E2)
From the list of given options.
A answers the question
Answer:
Kamira has 9 apples and John has 14 apples
Step-by-step explanation:
first you add 6+4 to get 10
then add 4+10 to get 14
Replace x with 2 and solve each equation:
1/2(2) + 4 = 1 + 4 = 5
2+ 6 -1/2(2) -2 = 8-3 = 5
The answer is:
both expressions equal 5 when substituting 2 for x because the expressions are equivalent.
Answer:
see below
Step-by-step explanation:
24 - 3 x = -27
Subtract 24 from each side
24-24 - 3 x = -27-24
-3x =-51
Divide each side by -3
-3x/-3 = -51/-3
x = 17
Check
24 -3(17) = -27
24 -51 = -27
-27 = -27